Studi Kelayakan Usaha Kopi Kekinian Berbasis Delivery-Only: Analisis Model Bisnis Tanpa Outlet Fisik di Era Digital - Putri Kemala Dewi Lubis; Agnes Avenia Barus; Enjel Elfrida Purba; Lusyana Sidebang; Novita Sari Br Kaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the feasibility and digital business model of AB.VA Coffee, a home-based coffee business that only provides delivery services and utilizes social media as its primary marketing and sales tool. The background of this study is based on the increasing popularity of coffee among the younger generation and the development of digital technology that has shifted consumer behavior towards online purchases. The method used is descriptive qualitative, with data collected through interviews, observations, and documentation of the business owner. Data analysis was carried out by reducing, displaying, and drawing conclusions. The results of this study indicate that AB.VA Coffee can adapt to digital advancements by implementing a direct delivery strategy that reduces operational costs and increases service efficiency. From a feasibility perspective, this business is declared feasible to run in terms of market, technical, and managerial aspects, although it still needs strengthening in the legal field for further development. Using the Business Model Canvas approach, it was found that all elements of the digital business model have been implemented simply but effectively, including product value, customer relationships, and distribution channels that rely on social media.